Comprehensive understanding of the mutant ‘giant’ Arthrospira platensis developed via ultraviolet mutagenesis - Lee, Changsu; Han, Sang-Il; Na, Ho; Kim, Zun; Ahn, Joon Woo; Oh, Byeolnim; Kim, Hyun Soo (Frontiers in Plant Science, 2024)
Introduction Cyanobacteria are typically of a size that can be observed under a microscope. Here, we present cyanobacteria of a size that can be observed with the naked eye. Arthrospira platensis NCB002 strain showed differentiated morphological characteristics compared to previously reported Arthrospira spp. Methods Arthrospira platensis NCB002 was obtained by the UV irradiation of Arthrospira sp. NCB001, which was isolated from freshwater and owned by NCell Co., Ltd. A. platensis NIES-39 was obtained from the National Institute for Environmental Studies (Tsukuba, Japan). We used various analytical techniques to determine its overall characteristics. Results and discussion The draft genome of strain NCB002 consists of five contigs comprising 6,864,973 bp with a G+C content of 44.3 mol%. The strain NCB002 had an average length of 11.69 ± 1.35 mm and a maximum of 15.15 mm, which is 23.4–50.5 times longer than the length (0.3–0.5 mm) of previously known Arthrospira spp., allowing it to be harvested using a thin sieve. Transcriptome analysis revealed that these morphological differences resulted from changes in cell wall formation mechanisms and increased cell division. Our results show that NCB002 has outstanding industrial value and provides a comprehensive understanding of it.